LEXICAL SEMANTIC FEATURES OF NEOLOGISMS IN MEDIA DISCOURSE - Abdurasulova Jasmina Akhmadjon kizi (Лучшие интеллектуальные исследования, 2024)
Abstract: In the history of human society, language arose from the need for exchange of communication during the joint work of people. The role of words, which are the smallest unit of language, is important in the process of becoming a speech of any language. Each word has an independent meaning and can be used freely in the structure of sentences and texts. Initially, when the theories of language learning appeared, hypotheses about its structure, structure and origin were studied. This article provides information about the lexical semantic features of neologisms in media discourse and their study. Аннотация: В истории человеческого общества язык возник из необходимости обмена сообщениями при совместной работе людей. Роль слов, которые являются мельчайшими единицами языка, важна в процессе становления речи любого языка. Каждое слово имеет самостоятельное значение и может свободно использоваться в структуре предложений и текстов. Первоначально, когда появились теории изучения языка, изучались гипотезы о его структуре, строении и происхождении. В данной статье представлена информация о лексико-семантических особенностях неологизмов в медиадискурсе и их изучении.